(untitled) (Texas Journal of Philology, Culture and History, 2022)
This article is devoted to the interpretation of pedagogical features and factors in the development of students’ communicative competence, as well as to the problems and solutions that arose as a result of research conducted by a number of scientists. In addition, pedagogical and psychological approaches to the development of communicative competence among students of higher educational institutions were analyzed.